Study On The Effects Of Natural Creams Infused With Sea Cucumber In The Abrasion Wound Healing Of Sprague Dawley Rats - Abdul Rahim, Norshuhaida (2016)
The study aims to evaluate the effects of the healing process on the abrasion wound by base natural cream formulation (BC), sea cucumber infusion in BC named as BCG formulation and presence of DEET in the BCGD formulation in comparison to normal saline which is a standard antiseptic treatment solution for abrasion wound